Rancang Bangun Sistem Informasi dan Penjualan Aksesoris Komputer Berbasis Web Pada Toko Sarjana Komputer - Romadhoni, Muhammad Arbiter Syahrul; Meimaharani, Rizkysari; Murti, Alif Catur (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The purpose of this journal is to design and build a web-based computer accessories information and sales system at Toko Sarjana Komputer. This system is expected to facilitate the sales management process, inventory, and customer service more effectively and efficiently. The methodology used in developing this system is the waterfall method, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. This system was built using the PHP programming language by utilizing the Laravel framework, with Visual Studio Code as the Integrated Development Environment (IDE) and MySQL as the database. PHP was chosen because of its flexibility and good ability to process data and easily integrate with various types of databases. Visual Studio Code provides a development environment that supports various extensions to simplify coding and debugging MySQL is used to manage large-scale data and support complex transactions. With this system, it is hoped that Toko Sarjana Komputer can improve operational efficiency and provide better service to customers. This system also provides a platform that is more accessible to customers to purchase computer accessories online.